Introduction to psychology - Cummings, Jorden A.; Sanders, Lee; Walinga, Jennifer; Jhangiani, Rajiv; University of Saskatchewan; BC Open Textbook Project; BCcampus (University of Saskatchewan Open Press, 2019)
"This introductory text has been created from a combination of original content and materials compiled and adapted from a number of open text publications, including Introduction to Psychology - 1st Canadian Edition (Stangor & Wallinga, 2014), the Noba Project, and Research Methods in Psychology - 3rd American Edition (Price, Jhangiani, Chiang, Leighton, & Cuttler, 2017). This version of the text includes a Key Terms list for each chapter, an expanded glossary, and H5P chapter self-tests"--BC Campus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes bibliographical references.
Description based on online version; Title from PDF (viewed on September 4, 2019).
Keywords: Psychology -- Textbooks; Electronic books